Fungsi Dinas Kesehatan Dalam Penyelenggaraan Sistem Kesehatan di Kabupaten Sikka (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
This study analyzes the Function of the Health Office in the implementation of health in Sikka Regency. The research method used is the Normative Judiciary method, using primary data and secondary data. Indonesia is one of the developing countries that has faced several fundamental strategic changes and challenges. The goal of the Indonesian nation is contained in the preamble to the 1945 Constitution which is held through national development, including health development. In supporting the implementation of health development, it requires support from a strong National Health System. Therefore, the Regency/City Health Office as the executor of affairs and services in the health sector also has the function of conducting supervision in their respective areas.The formulation of the problem in this study is: (1) How is the Regulation of the Function of the Health Office in the implementation of the health system in Sikka Regency? (2) What are the inhibiting factors of the Health Office in handling the implementation of the health system in Sikka Regency? From the results of the research, the author concludes that the function of the Health Office in the implementation of the health system in Sikka Regency is in accordance with the Regional Regulation of East Nusa Tenggara Province number 2 of 2018 concerning the implementation of Regional Health, Regional Regulation of Sikka Regency number 3 of 2021 concerning the Regional Health System, and Sikka Regent Regulation number 29 of 2016 concerning the position, organizational structure, duties and functions as well as work procedures of the Health Office. The obstacles or obstacles of the Health Office in the implementation of the Health System in Sikka Regency are seen from several factors, namely: limited human resources, budget and funding, infrastructure and health facilities, accessibility and transportation, and lack of public awareness and participation.